Biochemistry - Campbell, Mary K.; Farrell, Shawn O. (Stamford, CT : Cengage Learning, 2015)
Discover how the latest developments in biotechnology and genomics directly affect your life with this best-selling biochemistry text. This new edition reflects recent developments in stem cell research, cloning, and immunology, and offers revised coverage of major topics, such as Molecular Biology. Known for its logical organization and appropriate depth of coverage, Biochemistry, 8th Edition, balances scientific detail with readability that's ideal for those studying biochemistry for the first time. A unique magazine insert, Hot Topics in Biochemistry, introduces the latest advances in the field. State-of-the art visuals throughout the book help clarify concepts, while Biochemical Connections demonstrate how biochemistry affects other fields, such as health and sports medicine New in-text questions help you master key concepts of biochemistry, while end-of-chapter problem sets grouped by problem types help you master problem-solving skills.
Previous edition: 2012.
Includes bibliographical references and index.
Keywords: Biochemistry; Biochemistry -- Textbooks